USING THE HADITS OF IMAM AL-BUKHARI TO STRENGTHEN TEACHER-STUDENT RELATIONSHIPS (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article analyzes the universal significance of the spiritual heritage of Imam alBukhari, the sultan of hadiths, in the education of students and youth, as well as the pedagogical aspects of using Imam al-Bukhari's hadiths to strengthen teacher-student relationships in the scholar's works.
Keywords: Imam Bukhari; hadith; hadith scholar; enlightenment; education; teacher; student; teacher-student relationship; pedagogy; pedagogical idea; harmonious generation; child rearing; spiritual heritage